2020
DOI: 10.1080/22221751.2020.1830718
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Zika virus horizontal and vertical transmission in Aedes albopictus from Spain but not infectious virus in saliva of the progeny

Abstract: Aedes albopictus mosquitoes have been experimentally demonstrated to be a competent vector for Zika virus (ZIKV) in different countries, but there are still some gaps related to the importance of Ae. albopictus in ZIKV transmission. Recent studies on Spanish Ae. albopictus populations showed controversial results for ZIKV transmission and no studies have been performed yet to detect infectious ZIKV in saliva of progeny of infected female mosquitoes. Herein, the horizontal transmission (HT) and vertical transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…We observed significant VC differences (DE at 7 and 21 dpi, and TE at 21 dpi) between Ae. albopictus- LBV and -FCV after experimental infection with the African ZIKV strain, in agreement with the variations observed at the population level at different local geographical scales [ 33 , 44 , 45 ]. Nevertheless, our results clearly indicated that Ae.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We observed significant VC differences (DE at 7 and 21 dpi, and TE at 21 dpi) between Ae. albopictus- LBV and -FCV after experimental infection with the African ZIKV strain, in agreement with the variations observed at the population level at different local geographical scales [ 33 , 44 , 45 ]. Nevertheless, our results clearly indicated that Ae.…”
Section: Discussionsupporting
confidence: 86%
“…aegypti [ 37 , 41 , 42 ] and Ae. albopictus [ 43–46 ] populations from the Americas, Europe and Pacific Ocean Islands [ 37 , 44–46 ]. Although DAK84 strong infectiousness and transmissibility are a general trend that does not depend on the vector species ( Ae.…”
Section: Discussionmentioning
confidence: 99%
“…European Ae. albopictus are presumably a genetic mixture of populations from United States and La Reunion 43 , sharing similar profiles of ZIKV transmission with mosquitoes from La Reunion 16 , 44 , 45 . American ZIKV predominant during the 2015–2016 epidemic, was efficiently transmitted by Ae.…”
Section: Discussionmentioning
confidence: 99%
“…ZIKV has become a threat to public health because it has been demonstrated to cause microcephaly in neonates and has rapidly spread in many countries ( 42 , 43 ). Most experiments have focused on ZIKV transmission in Ae.…”
Section: Discussionmentioning
confidence: 99%